Fabrication of 3D Printed poly(lactic acid) strut and wet-electrospun cellulose nano fiber reinforced chitosan-collagen hydrogel composite scaffolds for meniscus tissue engineering. (October 2022) - Gunes, Oylum Colpankan; Kara, Aylin; Baysan, Gizem; Bugra Husemoglu, Resit; Akokay, Pinar; Ziylan Albayrak, Aylin; Ergur, Bekir Ugur; Havitcioglu, Hasan
The main goal of the study was to produce chitosan-collagen hydrogel composite scaffolds consisting of 3D printed poly(lactic acid) (PLA) strut and nanofibrous cellulose for meniscus cartilage tissue engineering. For this purpose, first PLA strut containing microchannels was incorporated into cellulose nanofibers and then they were embedded into chitosan-collagen matrix to obtain micro- and nano-sized topographical features for better cellular activities as well as mechanical properties. All the hydrogel composite scaffolds produced by using three different concentrations of genipin (0.1, 0.3, and 0.5%) had an interconnected microporous structure with a swelling ratio of about 400% and water content values between 77 and 83% which is similar to native cartilage extracellular matrix. The compressive strength of all the hydrogel composite scaffolds was found to be similar (∼32 kPa) and suitable for cartilage tissue engineering applications. Besides, the hydrogel composite scaffold comprising 0.3% (w/v) genipin had the highest tan δ value (0.044) at a frequency of 1 Hz which is around the walking frequency of a person. According to the in vitro analysis, this hydrogel composite scaffold did not show any cytotoxic effect on the rabbit mesenchymal stem cells and enabled cells to attach, proliferate and also migrate through the inner area of the scaffold. In conclusion, the produced hydrogel composite scaffold holds great promise for meniscus tissue engineering.